The Influence of Academic Supervision and Organizational Culture on the Professionalism of Public Middle School Teachers in Pemulutan District - Tihuriyanti, Ivanti; Ahyani, Nur; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2024)
Supervision in schools helps teachers and supervisors learn about daily tasks, providing better services to students and schools as effective learning communities. Teacher professionalism is the teacher’s ability to manage learning well. A teacher can manage learning if he masters the subject matter, manages the class well, understands various learning strategies and methods, and uses existing learning media and resources. The principal’s leadership and school organizational culture also play a role in increasing teacher professionalism. A conducive working atmosphere greatly influences the quality of teacher work. Organizational culture influences the performance and systems in schools, influencing school effectiveness. This quantitative research with a descriptive approach aims to reveal the influence of academic supervision and organizational culture on the professionalism of SMP Negeri teachers in the Pemulutan District. The research results show that academic supervision has a significant effect on teacher professionalism, while organizational culture has a significant effect.